The Effect of Tax Avoidance, Multinationality, and Profitability on Corporate Transfer Pricing Decisions: a Systematic Literature Review - Agusman Sianturi; Dana Farhana; Luk Luk Fuadah (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the influence of tax avoidance, multinationality, and profitability on transfer pricing decisions in multinational companies through the Systematic Literature Review (SLR) method. This study uses 50 national and international articles indexed by Scopus and Sinta with a publication period of 2019–2024. The results of the study show that transfer pricing practices are influenced by three main factors, namely tax avoidance, multinationality, and profitability. The tax avoidance factor has proven to be the main driver for companies to carry out transfer pricing to divert profits to countries with low tax rates. Multinationality has a positive effect because the wider the cross-border operation, the greater the opportunity for transfer pricing practices. However, profitability shows mixed results; Some studies show positive influences, while others find negative influences depending on the industry context, tax regulations, and corporate governance. These findings confirm the importance of monitoring and applying the arm's length principle to prevent the abuse of transfer pricing in multinational companies.